Behavioural risk patterns in adolescents with excess weight participating in the PRALIMAP-INÈS trial - Chantal Julia; Abdou Omorou; Edith Lecomte; Johanne Langlois; Mathilde Touvier; Serge Hercberg; Serge Briançon; Emmanuelle Kesse-Guyot; Francis Guillemin; the PRALIMAP-INÈS Trial Group (Cambridge University Press, 2023)
Abstract Objective: To investigate clustering of risk behaviours in adolescents with excess weight. Design: Cross-sectional analysis of baseline data from the PRALIMAP-INÈS trial. Information on food frequency consumption (fruit, vegetables, sugary products and beverages), physical activity, sedentary behaviour (week and weekend days), smoking and alcohol consumption (current frequency and intoxication episodes) and socio-demographic data was collected using self-reported questionnaires. Behavioural risk factors were entered as categorical variables in a two-step clustering procedure: multiple correspondence analysis followed by hierarchical clustering. Associations between cluster membership and socio-demographic variables were investigated using multivariable multinomial logistic regression. Setting: French PRALIMAP-INÈS trial. Participants: Adolescents with excess weight. Results: A total of 1391 participants (13-18 years old, 58·2 % female) were included in the analysis, which resulted in the identification of four groups of participants, including, respectively, 543 (39·0 %), 373 (26·8 %), 246 (17·7 %) and 229 (16·5 %) participants. Clusters 1 and 4 showed associations of rather healthy behaviours (high physical activity and low consumption of sugary products; high consumption of fruit and vegetables, respectively), while clusters 2 and 3 showed associations of rather unhealthy behaviours (high sedentary behaviour and low consumption of fruit and vegetables; smoking and alcohol consumption, respectively). Both social status and family structure were associated with cluster membership. Conclusions: Risk behaviour patterns in adolescents with excess weight were clustered in both healthier and less healthy ways, with a complex interplay with socio-demographic factors.